2014
DOI: 10.1016/j.comppsych.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between stress and the BDNF Val66Met polymorphism in depression: A systematic review and meta-analysis

Abstract: Background: Major depression is a disabling psychiatric illness with complex origins. Life stress (childhood adversity and recent stressful events) is a robust risk factor for depression. The relationship between life stress and Val66Met polymorphism in the brain-derived neurotrophic factor (BDNF) gene has received much attention. The aim of the present work was to review and conduct a meta-analysis on the results from published studies examining this interaction. Methods: A literature search was conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 66 publications
2
62
1
1
Order By: Relevance
“…However, available data do not support a significant effect of rs6265 on MDD susceptibility, as indicated by meta-analyses (Gratacos et al 2007;Gyekis et al 2013) that also provided negative findings for other BDNF SNPs (11757C/G, 270T/C, 712A/G and rs988748). Conversely, the rs6265 Met allele was demonstrated to moderate the relationship between life stress and depression (Hosang et al 2014;Gutierrez et al 2015).…”
Section: Genetic Polymorphismsmentioning
confidence: 95%
“…However, available data do not support a significant effect of rs6265 on MDD susceptibility, as indicated by meta-analyses (Gratacos et al 2007;Gyekis et al 2013) that also provided negative findings for other BDNF SNPs (11757C/G, 270T/C, 712A/G and rs988748). Conversely, the rs6265 Met allele was demonstrated to moderate the relationship between life stress and depression (Hosang et al 2014;Gutierrez et al 2015).…”
Section: Genetic Polymorphismsmentioning
confidence: 95%
“…Our findings, together with prior adolescent studies (Chen et al 2012;Cruz-Fuentes et al 2014;Gottfredson et al 2014), support the propostion that BDNF Val66Met 9 Environment might vary between adolescents and adults. Specifically, the Val version of BDNF appears to confer heightened susceptibility to environmental influences in the case of youth, whereas the Met version of BDNF operates in this manner with regard to depression and adversity in the case of adults (see meta-analysis in Hosang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of G 9 E studies of mostly even if not exclusively adult participants revealed that it was Met-BDNF carriers who were most prone to depression in the face of life stress (Hosang et al 2014). Notably, though, a study of Chinese adolescents found that it was Val-BDNF carriers who proved most susceptible to depressive symptoms in the face of stressful life events (Chen et al 2012).…”
Section: Bdnf Val66met 3 Environment On Depressionmentioning
confidence: 99%
“…Studies have demonstrated that the alteration in BDNF expression is closely associated with chronic stress-induced depression [33]. Infusion of BDNF into the brains produces antidepressant-like behavioral effects in rats [34].…”
Section: Discussionmentioning
confidence: 99%